Effects of HIV knowledge on accepting attitudes toward people living with HIV: The case of Southern Vietnam - Tram N.T. Huyen; Somying Pumtong; Sermsiri Sangroongruangsri; Luerat Anuratpanich (GarVal Editorial Ltda., 2023)
Context: Increasing thorough knowledge and adopting a positive outlook are crucial intervention strategies in the campaign against HIV transmission. However, the stigma associated with the disease frequently causes discrimination and other human rights violations that affect the well-being of people living with HIV (PLWH). Aims: To evaluate the effects of HIV knowledge on accepting attitudes among the Vietnamese population toward PLWH. Methods: A cross-sectional, self-administered, paper-based survey was conducted. Participants who provided correct answers to 13 out of the 18 questions were considered to have good knowledge, and those who chose "yes" as the response to the first three attitude questions and "no" to the last one were regarded as exhibiting appropriate attitudes. A logistic regression model was used to identify the association between knowledge and attitudes. Results: Among the participants (average age: 23.7 ± 6.4), 90.9% believed they were not at risk of HIV infection, and only 488 (39.8%) had good HIV knowledge. A low proportion (less than 20%) of them exhibited appropriate attitudes. A favorable attitude toward PLWH was significantly correlated with being male and having extensive HIV knowledge. Conclusions: While almost half of Vietnamese adults had good knowledge about HIV transmission, a significant proportion still lacked HIV knowledge and stigmatized people living with HIV. These findings suggest a need for targeted public health interventions, such as a national health education program that emphasizes family life and HIV/AIDS education, to improve knowledge and reduce stigmatization toward PLWH in Vietnam.